(untitled) - Machlup, Fritz (Princeton, N.J., 1962)
The Production and Distribution of Knowledge in the United States marked the beginning of the study of our postindustrial information society. Austrian-born economist Fritz Machlup had focused his research on the patent system, but he came to realize that patents were simply one part of a much bigger "knowledge economy." He then expanded the scope of his work to evaluate everything from stationery and typewriters to advertising to presidential addresses--anything that involved the activity of telling anyone anything. The Production and Distribution of Knowledge in the United States then revealed the new and startling shape of the U.S. economy.
Keywords: Thông tin khoa học,Information science; Hoa Kỳ,United States